Acute respiratory failure requiring mechanical ventilation in severe chronic obstructive pulmonary disease (COPD). Issue 17 (April 2018) - Gadre, Shruti K.; Duggal, Abhijit; Mireles-Cabodevila, Eduardo; Krishnan, Sudhir; Wang, Xiao-Feng; Zell, Katrina; Guzman, Jorge
Abstract : Abstract: There are limited data on the epidemiology of acute respiratory failure necessitating mechanical ventilation in patients with severe chronic obstructive pulmonary disease (COPD). The prognosis of acute respiratory failure requiring invasive mechanical ventilation is believed to be grim in this population. The purpose of this study was to illustrate the epidemiologic characteristics and outcomes of patients with underlying severe COPD requiring mechanical ventilation. A retrospective study of patients admitted to a quaternary referral medical intensive care unit (ICU) between January 2008 and December 2012 with a diagnosis of severe COPD and requiring invasive mechanical ventilation for acute respiratory failure. We evaluated 670 patients with an established diagnosis of severe COPD requiring mechanical ventilation for acute respiratory failure of whom 47% were male with a mean age of 63.7 ± 12.4 years and Acute physiology and chronic health evaluation (APACHE) III score of 76.3 ± 27.2. Only seventy-nine (12%) were admitted with a COPD exacerbation, 27(4%) had acute respiratory distress syndrome (ARDS), 78 (12%) had pneumonia, 78 (12%) had sepsis, and 312 (47%) had other causes of respiratory failure, including pulmonary embolism, pneumothorax, etc. Eighteen percent of the patients received a trial of noninvasive positive pressure ventilation. The median duration of mechanical ventilation was 3 days (interquartile range IQR 2–7); the median duration for ICU length of stay (LOS) was 5 (IQR 2–9) days and the median duration of hospital LOS was 12 (IQR 7–22) days. The overall ICU mortality was 25%. Patients with COPD exacerbation had a shorter median duration of mechanical ventilation (2 vs 4 days; P = .04), ICU (3 vs 5 days; P = .01), and hospital stay (10 vs 13 days; P = .01). The ICU mortality (9% vs 27%; P < .001), and the hospital mortality (17% vs 32%; P = .004) for mechanically ventilated patients with an acute exacerbation of severe COPD were lower than those with other etiologies of acute respiratory failure. A 1-unit increase in the APACHE III score was associated with a 1% decrease and having an active cancer was associated with a 45% decrease in ICU survival ( P < .001). A discharge home at the time of index admission was associated an increased overall survival compared with any other discharge location ( P < .001). We report good early outcomes, but significant long-term morbidity in patients with severe COPD requiring invasive mechanical ventilation for acute respiratory failure. A higher APACHE score and presence of active malignancy are associated with a decrease in ICU survival, whereas a discharge home is associated with an increase in the overall survival.